ANTARA IDENTITAS KULTURAL DAN PLURALITAS WILAYAH: MENIMBANG NASIB MENTAWAI DALAM WACANA KEISTIMEWAAN MINANGKABAU - Frans Tory Damara Pradipta (Jurnal Suara Politik, 2026)
The discourse on establishing a Special Region of Minangkabau has resurfaced in the regional political dynamics of West Sumatra. The proposal is grounded in historical and cultural legitimacy, particularly the continuity of the nagari system and Minangkabau customary institutions, which are considered distinctive within Indonesia’s framework of asymmetric decentralization. However, the administrative territory of West Sumatra also encompasses the Mentawai Islands, whose ethnic background, historical trajectory, and social structure differ fundamentally from Minangkabau traditions. This article examines the political and administrative implications of the special status discourse for the position of Mentawai within the region’s identity configuration. Employing a qualitative approach through literature review and discourse analysis of regulations, academic works, and media reports, the study draws on the concepts of asymmetric decentralization and identity politics in regional governance. The findings indicate that the construction of special status largely relies on the assumption of Minangkabau cultural dominance, while Mentawai tends to be positioned peripherally in the discourse. This imbalance raises critical questions concerning representation, recognition, and the limits of identity-based legitimacy within a plural administrative territory. The article argues that any design of special status that fails to explicitly acknowledge internal plurality risks reproducing homogenization in a heterogeneous regional space.